Constructivism in the ESL writing classroom: A case for collaborative essay writing / Noor Hanim Rahmat - Rahmat, Noor Hanim (Universiti Teknologi MARA Cawangan Kedah, 2014)
This paper reports a case study on how movies and collaborative writing influence ESL writing classroom. The Constructivist theory emphasizes that learning environment can be effective when it emphasizes the use of authentic tasks in a meaningful context (Jonassen, 1999). Instead of learning academic writing from textbook context which students may neither be familiar with nor find them interesting, movies help bring fun into the academic writing classroom. Using movies also helps make learning authentic as students learn from something they are familiar with. Furthermore, learners need to form mental images when they learn in the classroom and movies can help to do that. In addition to that, Mulligan & Garofalo (2011) found that collaborative writing enhances students’ writing and lowers anxiety associated with completing the task alone. This study involves students using the contents of a movie to write academic essays using collaborative approach. Findings of this research will reveal interesting implication in the teaching of writing.